Measuring the Young’s modulus of individual lithium whiskers - Wenbo Zhai; Hongsheng Shi; Wei Liu; Yi Yu (Proceedings of the National Academy of Sciences, 2025)
The primary challenge hindering widespread adoption of lithium (Li) anodes is the safety risks of short circuits owing to the penetration of Li whiskers, where their mechanical property plays a crucial role. However, measurement of the overall Young’s modulus of individual Li whiskers with solid electrolyte interphase (SEI) remains elusive. Here, via an in situ electric-field-induced resonance method, the Young’s modulus of individual electrochemically deposited Li whiskers along <211> is measured to be 3.2 ± 0.2 GPa in a transmission electron microscope, lower than that of pure Li metal, suggesting that hard short circuits induced by mechanical penetration are expected to have a low probability of occurrence. Quantitative analysis reveals that a simple linear combination of the Young’s moduli of pure Li metal and the SEI, based on a linear mixed model, fails to account for the reduced Young’s modulus. With the aid of atomic-level imaging and simulations, the lower value is ascribed to intricate interfacial microstructures, including highly-crystalline-Li|poorly-crystalline-Li, Li|Li 2 O, Li|organic, and others.